2010
DOI: 10.2527/jas.2009-2253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary omega-3 fatty acid source on plasma and red blood cell membrane composition and immune function in yearling horses1

Abstract: To determine the effect of different sources of dietary n-3 fatty acids (FA) on plasma and red blood cell (RBC) FA composition and immune response, 18 Quarter Horse yearlings were randomly and equally assigned to 1 of 3 treatments: encapsulated fish oil (n = 6), milled flaxseed (n = 6), or no supplementation (control, n = 6). Fish oil contained 15 g of eicosapentaenoic acid (C20:5n-3) and 12.5 g of docosahexaenoic acid (C22:6n-3), and flaxseed contained 61 g of alpha-linolenic acid (C18:3n-3) per 100 g of FA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…There is limited conversion of ALA to DHA in humans (Burdge et al, 2001;Arterburn et al, 2006). As stated before, in horses, supplementation with ALA did not lead to increases in circulating DHA (Hansen et al, 2002;Vineyard et al, 2010), only EPA. Feeding of n-3 PUFA to horses may increase circulating levels and increase incorporation into muscle tissue.…”
Section: Specific Horse Studiesmentioning
confidence: 75%
See 1 more Smart Citation
“…There is limited conversion of ALA to DHA in humans (Burdge et al, 2001;Arterburn et al, 2006). As stated before, in horses, supplementation with ALA did not lead to increases in circulating DHA (Hansen et al, 2002;Vineyard et al, 2010), only EPA. Feeding of n-3 PUFA to horses may increase circulating levels and increase incorporation into muscle tissue.…”
Section: Specific Horse Studiesmentioning
confidence: 75%
“…Additionally, they have been used as supplements in equine diets. Horse studies indicated that supplementation with ALA would not lead to increases in circulating DHA (Hansen et al, 2002;Vineyard et al, 2010), only increases in circulating EPA.…”
Section: Dietary N-3 and N-6 Long-chain Polyunsaturated Fatty Acids (mentioning
confidence: 99%
“…Dietary supplementation with more than 3.3 g EPA + DHA/100 kg BW daily (and in some studies up to 20.7 g EPA + DHA/100 kg BW) has been reported to decrease tumour necrosis factor‐α (TNF‐α), interleukin (IL)‐1, IL‐2, IL‐6 and interferon (IFN)‐γ by mononuclear cell (Calder, 2001). Vineyard et al. (2010) reported that horses fed FO containing 15 g EPA and 12.5 g DHA had higher proportions of EPA, DHA, RBC (red blood cells) and arachidonic acid in their plasma.…”
Section: Immunitymentioning
confidence: 99%
“…The presence of EPA and DHA was associated with the seasonal availability of ALA in the diet of a grazing horse. In another study (Vineyard et al., ), the ALA provided by pasture grass may have been sufficient to allow EPA and DHA synthesis, which were at sufficiently high concentrations to be detectable in RBC of horses on both control and linseed diets.…”
Section: Discussionmentioning
confidence: 93%
“…Vineyard et al. () reported a greater impact on plasma and RBC FA composition when linseed was added to the diet. When sunflower oil was added to the diet, the observed significant changes compared to control diet were mainly due to LA presence.…”
Section: Discussionmentioning
confidence: 99%